A semiótica da luz na tradução de O Quinze, de Rachel de Queiroz, às telas e a outras páginas - Lovatel, Marília Ribeiro (2017)
This investigation refers to the intersemiotic translation of the novel O Quinze, a work published in 1930 by the writer Rachel de Queiroz, according to the categories of transparency and opacity. The analysis intends to point out the occurrence of a semiotic of light, motivated by the metaphor of the “glass tile”, suggested in a poem by the mentioned novelist, in the translated text and in the developments that extrapolate the original textual plan. The analysis in question develops in two levels. The first one is composed by the challenge that represents the film adaptation of the mentioned literary work, by passing through its adaptation to comic books, video and TV; and the second one refers to the dichotomous literary relations of transparency versus opacity, studied within the context of a semiotic of light. Based on the discursive semiotic of Greimas and his followers, specially Denis Bertrand, Diana Luz Pessoa de Barros and José Luiz Fiorin, and of the intersemiotic translation proposed by Roman Jakobson, this study culminates in a quantitative and qualitative survey of the occurrence of transparency and opacity in the film adaptation of O Quinze, which is understood as a translation of the namesake novel, realized by Jurandir Oliveira in 2004. By crossing the mentioned theoretical references, the reading of the literary and movie texts, by admitting that the metaphor of the glass tile is an integrating category of the compared study, we conclude that it is possible to recognize either the opacity or the transparency effect in the work of Jurandir Oliveira.